2008
DOI: 10.2214/ajr.08.1057
|View full text |Cite
|
Sign up to set email alerts
|

Screw Impingement on the Extensor Tendons in Distal Radius Fractures Treated by Volar Plating: Sonographic Appearance

Abstract: W199age, 54 years). Three right wrists and six left wrists were affected. Four patients were referred with a presumptive diagnosis of complete extensor pollicis longus (EPL) tear and three had a diagnosis of tenosynovitis; one, a dorsal mass; and one, a ganglion cyst. Patients presented with local pain (n = 8), swelling (n = 7), and inability to extend the distal phalanx of the thumb (n = 4). Informed consent was obtained to search patients' data retrospectively. Institutional review board approval was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 11 publications
1
55
0
Order By: Relevance
“…In a pictorial essay, Guillin et al illustrated examples of upper and lower extremity hardware impingement of soft tissue, muscle, tendons, nerves, vessels, and bursa diagnosed with sonography that were not appreciated on radiography or MRI. Bianchi et al described the sonographic diagnosis of tendon injuries after volar plating of distal radius fractures and discussed the potential limitations of radiography, fluoroscopy, and MRI in demonstrating injuries at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…In a pictorial essay, Guillin et al illustrated examples of upper and lower extremity hardware impingement of soft tissue, muscle, tendons, nerves, vessels, and bursa diagnosed with sonography that were not appreciated on radiography or MRI. Bianchi et al described the sonographic diagnosis of tendon injuries after volar plating of distal radius fractures and discussed the potential limitations of radiography, fluoroscopy, and MRI in demonstrating injuries at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Bianchi et al [49] have reported that 12 protruding screws are identified through the use of sonography with the mean length of protrusion of 2.7 mm from the radial cortex. Radiological examination have been used in clinical situation to assess the screw bone interface [53].…”
Section: Assessment Of Screw-bone Implantmentioning
confidence: 99%
“…3). Tenosynovitis can be diagnosed easily with the presence of an effusion or thickening of the synovium around the tendons (15).…”
Section: Tendonsmentioning
confidence: 99%